If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = r + -3 Reorder the terms: 4 = -3 + r Solving 4 = -3 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 4 + -1r = -3 + r + -1r Combine like terms: r + -1r = 0 4 + -1r = -3 + 0 4 + -1r = -3 Add '-4' to each side of the equation. 4 + -4 + -1r = -3 + -4 Combine like terms: 4 + -4 = 0 0 + -1r = -3 + -4 -1r = -3 + -4 Combine like terms: -3 + -4 = -7 -1r = -7 Divide each side by '-1'. r = 7 Simplifying r = 7
| 4x+9=-8x-13 | | 5x+10=3x | | 5(x)(2)-8=10 | | p=42-5q-q | | 7=p+9/3 | | -8x+3=27 | | 34=14-4p | | x^2-10+58+x=180 | | 17=x/2+9 | | x(5)(2)-8=10 | | 150-5x=4x+24 | | -6=(-8)+n/2 | | -3(4n-6)=-6-6n | | 7x+9-6(11+1)= | | 55.25=h*.85 | | 9z^2-3z+1=0 | | 5n+3=43 | | 25+10-5+5= | | 3(3)-y=4 | | 2x(2)+8=10 | | 3(2)-y=4 | | 2x^3+5x^2-200x-500=0 | | 50+1.99x=3.99x | | (17+a)*(17+a)=2209 | | x-.24=x/3+7.75 | | 32u-1-12u=22u-66 | | 7h-7+2h=7 | | 12x-9y=36 | | 9x^2-24x+64=0 | | 2a+2*3=36 | | (17+a)x(17+a)=2209 | | 45+.12m=49.32 |